Meningkatkan kemampuan Membaca Permulaan pada Anak Kelompok A PAUD Sambela Kota Bengkulu - Vivi Puspa Indria; Sumarsih Sumarsih; Nesna Agustriana (Jurnal Ilmiah POTENSIA, 2017)
This Research aims to improving early reading ability through Glenn Doman Reading Method in children group A PAUD Sambela in Bengkulu City. The type of research is used Classroom Action Research (CAR). The research is done in two cycles. Every cycles it was done in 3 times meeting. The subject is the children group A as many as 10 children consist of 6 boys and 4 girls. Data collection techniques used is observation. The data analyzing was by used statistical techniques with average formula. The results of the study indicate that children’s early reading ability can be improved through Glenn Doman Reading Method. This research proves that early reading ability through Glenn Doman Method can directly introduce the child to the whole word instead of the letters. Therefore advisable to group A teachers to use Glenn Doman Reading Method in improving early reading ability by introducing the child to a word consisting of two syllables first, and then raised on words that have more than two syllables.